The Higher Earning in America: Are 529 Plans a Good Way to Save for College?. Issue 2 (3rd April 2017) - Pressman, Steven; Scott, Robert H.
Abstract: This article studies whether 529 plans are an effective way for most people to save for college. The 529 plans were created in 1996 to help low- and middle-income American families save for college. Since this time they have adopted more tax advantages and grown substantially as a result. While total balances in 529 plans now exceed $250 billion, less than 3.0 percent of households have a 529 plan. And the majority of 529 plan accounts are held by the wealthiest households. Low- and middle-income households receive little tax savings from investing in 529 plans, and some states count these plans against financial aid. Also, 529 plans are complicated, rules vary by state, and fund management fees tend to be high. Thus, 529 plans are not the panacea to college affordability.